Dual chamber solar dryers: Maximizing thermal performance for diverse product drying - Prabhu, C. Naveen; Dhanushkodi, S.; Sudhakar, K. (Elsevier B.V., 2025)
The drying of agricultural and marine products demands specific temperature conditions. Existing dryers are often limited to a single product type and have a limited temperature range. This research addresses this challenge by developing a hybrid dryer that efficiently uses solar energy and biomass heating to dry several products. This dryer consists of a dual-chamber solar flat plate collector (FPC). One steel chamber integrates a biomass heater and a polycarbonate chamber connected exclusively to the FPC. Marine items requiring higher temperatures ranging from 78 to 85 degrees Celsius are processed in a steel drying chamber with a 40 kg capacity. In contrast, the agricultural products requiring 50-65°C are dried in a polycarbonate drying chamber. Experimental tests involved drying 3 kg of anchovy fish in the steel chamber, 2 kilograms of Indian gooseberry, and 1 kg of Moringa oleifera leaves in the polycarbonate chamber. The drying chamber's moisture content, drying time, and efficiency are assessed and compared with traditional sun drying techniques. The hybrid drying mode achieved a target moisture content of 8% (w.b) within 9 hours with an average efficiency of 36%. In comparison, solar forced drying achieved the desired moisture content of 4% for Indian gooseberries in 6 hours and 5.2 % for drumstick leaves in 2 hours, with an average system efficiency of 25%. Notably, the hybrid forced mode proved twice as fast as open sun drying, presenting versatile drying solutions for small-scale farmers. Future improvements may include scaling up the design, integrating automation and monitoring systems to enhance usability.